A Multiband Monopole Antenna with the Inverted-Trapezoidal CPW Feeding - Quanqi Zhang; Yuanxin Li; Zhixi Liang; Hong-Zhou Tan; Yunliang Long (International Journal of Antennas and Propagation)
A multi-band monopole antenna with the improved inverted-trapezoidal coplanar waveguide (CPW) feeding is presented. The antenna has a simple planar structure, and occupies an area of 15 mm × 50 mm. The proposed antenna consists of an improved inverted-trapezoidal CPW-fed patch, and a series of monopole strips with different length. This monopole antenna utilizes the advantages of the CPW feeding to simplify the structure of the antenna into a single metallic level and achieve high antenna gain. The improved inverted-trapezoidal CPW-fed patch and a meander shorting strip lead to a better impedance matching result and multi-band operation. The experimental results of the proposed antenna are shown and discussed. The antenna generates two wide bands centered at about 900 and 2200 MHz to cover the GSM850/GSM900/DCS/PCS/UMTS/LTE2300/2500 bands and the 2.4 GHz WLAN operation. Meanwhile the antenna covers the 4 G bands of China Telecom (2370–2390 MHz/2635–2655 MHz), China Unicom (2300–2320 MHz/2555–2575 MHz) and China Mobile (1880–1900 MHz/2320–2370 MHz/2575–2635 MHz), too.